Painted alchemists : early modern artistry and experiment in the work of Thomas Wijck - Berry Drago, Elisabeth (Amsterdam studies in the Dutch golden age., 2019)
Thomas Wijck's painted alchemical laboratories were celebrated in his day as "artful" and "ingenious." They fell into obscurity along with their subject, as alchemy came to be viewed as an occult art or a fool's errand. But these unusual pictures challenge our understanding of early modern alchemy--and of the deeper relationship between chemical workshops and the artists who represented them. The work of artists, like the work of alchemists, contained intellectual-creative and manual-material aspects. Both alchemists and artists claimed a special status owing to their creative powers. Wijck's formation of an artistic and professional identity around alchemical themes reveals his desire to explore this curious territory, and ultimately to demonstrate art's superior claims to knowledge and mastery over nature. This book explores one artist's transformation of alchemy and its materials into a reputation for virtuosity--and what his work can teach us about the experimental early modern world.--